WE THAT ARE YOUNG - PRETI TANEJA (HARYANA PENGUIN, 2017)
Jivan Singh, the bastard scion of the Bapuji family, returns to his childhood home after a long absence - only to witness the unexpected resignation of the ageing Devraj Bapuji from the vast corporation he founded, Company India. On the same day, Sita, Devraj's youngest daughter, absconds - refusing to submit to the marriage her father wants for her. Meanwhile, Radha and Gargi, Sita's older sisters, are left to run the Company. And so begins a brutal, deathly struggle for power, ranging over the Palaces and slums of New Delhi, the luxury resorts and spas of Amritsar and Srinagar. We That Are Young is a modern-day King Lear that bursts with energy and fierce, beautifully measured rage. Set against the backdrop of the Anti-Corruption Riots in 2011-2012, it provides startling insights into life in modern India, the clash of old and new, the breakneck pace of life in one of the world's fastest developing economies - and the ever-present spectre of death. More than that, this is a novel about the human heart and its breaking point.
Keywords: ENGLISH NOVEL; INDIAN ENGLISH NOVEL